RAAS: Ransomware-as-a-Service - Salvi, Harshada Umesh (International Journal of Computer Sciences and Engineering, 2019)
Ransomware is a kind of malicious code, or malware, designed to deny access to a computer system or data till a ransom is paid. It generally spreads through phishing emails or by inadvertently visiting associate infected web site. Ransomware is not a brand new threat to the cyber world. Its origins dates back a few years. Over time, this threat has become more and more vicious and harmful. While people were contending with this cyber threat, cybercriminals moved one step further by providing ransomware-as-a-service (RAAS). This paper presents the overview of the RaaS kits. It focuses on the general working of the RaaS, five RaaS kits – Philadelphia, Stampado, Frozr Locker, Satan, Jokeroo. Nowadays it has become increasingly easy to create and launch ransomware, irrespective of skill. Anyone with an ill intent and access to the dark net can advertise the ransomware kits the way an online retailer promotes clothing or toys. This paper provides different defensive measures against ransomwares to individuals and organizations that they can adopt to protect themselves from the threat of ransomwares.